Spy School : British invasion - Gibbs, Stuart, 1969- (New York : Simon & Schuster Books for Young Readers, 2019)
"Follows the spies-in-training on a hunt to find the leader of the evil organization SPYDER and take them down once and for all"--
Map on lining papers.
Ages 8-12.
Keywords: Friendship -- Juvenile fiction; Schools -- Juvenile fiction; England -- Juvenile fiction; Spy fiction; Action and adventure fiction